PENGARUH UKURAN PERUSAHAAN, TINGKAT PENJUALAN PERUSAHAAN, DAN REPUTASI KAP PADA PERGANTIAN KAP - Muria Sidhi, Bagus Ananta Diva; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2015)
Auditor Switching occurs because increasing operating of Public Accounting Firm. Auditor Switching may occur voluntary or mandatory. This study aims to determine the effect of firm size, firm growth and reputation of Public Accounting Firm to auditor switching in manufacturing companies that listed on the Indonesia Stock Exchange. Purposive sampling was used in this study as the sampling technique. Logistic regression analysis used in this study to determine the effect of firm size, firm growth, reputation of Public Accounting Firm to auditor switching. The result can be shown in this research is the firm size variable has no effect on the auditor switching, no influence of firm growth variabel on auditor switching, and reputation of the Public Accounting firm has a  significant influence on the auditor switching.
Keywords: firm size, firm growth, reputation of Public Accounting Firm, Auditor Switching